Electrochemotherapy with bleomycin of different types of cutaneous tumours in a ferret (Mustela putorius furo) - Račnik, Joško (Radiology and oncology (Ljubljana), 2018)
Mast cell tumour, sebaceous gland adenoma, and less common squamous papilloma are skin tumours in ferrets (Mustela putorius furo), and early excisional surgery is usually the treatment of choice. The aim of our study was to investigate the effectiveness of electrochemotherapy (ECT), a new, minimally invasive non-surgical method, as first treatment option of different types of ferret skin tumours located on surgically difficult sites. Materials and methods A 5-year-old castrated male ferret with two cutaneous masses, presenting 4 months apart and a 7-year-old spayed female ferret with two cutaneous masses, that appeared simultaneously on two locations are presented. In the first patient, both masses were diagnosed as mast cell tumours, and in the second patient, squamous papilloma and sebaceous adenoma were diagnosed. One session of ECT with bleomycin injected intratumourally was applied in all tumours. Results Complete response (CR) of all tumours was obtained, without recurrence during observation period of 15 months after ECT for first tumour and 11 months after ECT of the tumour located on the right hock in first patient, and 8 months after treatment for the second patient. Conclusions In present study, ECT with bleomycin proved to be safe and effective against different cutaneous tumours in ferrets. Due of good results, low cost and relatively easy procedure, ECT could be the treatment of choice instead of surgery for the selected skin tumours in ferrets.
Keywords: Bleomycin; Electrochemotherapy; Ferrets; Neoplasms; Therapy